Comparison of oral health and nutritional status between hospitalised and non-hospitalised elderly in a selected urban Malaysian population / Vaishali Malhotra - Vaishali, Malhotra (2019)
Introduction Malaysia is rapidly advancing towards the status of an ageing nation. Demographic transitions pose major challenges for health care providers in planning and providing effective and holistic health care to institutionalized older people. Health authorities are experiencing an increasing public health problem; the growing burden of oral diseases among older people. The concept of oral health has evolved from just having healthy teeth. Holistic oral health includes excellent oral function which is the ability to smile, speak, swallow and chew competently, and without pain; bringing about improvement in general health and increased self-esteem. However, in the present scenario, the oral health of older Malaysians is far from optimal. Aim The purpose of this study was to compare the oral health and nutritional status between the hospitalised and non-hospitalised urban elderly population. Materials and Methods An observational, comparative cross-sectional study was conducted. Cases were a convenience sample was obtained from the geriatric wards at the University of Malaya Medical Centre while matched controls were selected from the Malaysian Elders Longitudinal Research (MELoR) study. A structured questionnaire was administered face-to-face to obtain socio-demographics, medical history, oral health related knowledge, attitude and practices, and nutrition status. Clinical assessments including dentition status, salivation status and periodontal health status were conducted by trained, calibrated dentists. iv Results 148 (74 hospitalised and 74 non-hospitalised) participants, mean age = 80.76 (±7.4) years, 54.1% women, age and gender matched, were recruited. The mean number of missing teeth was 23.12 (±10.1) in the hospitalised group and 17.34 (±5.5) in the nonhospitalised group (p < .001). Significantly fewer hospitalised individuals felt it was important to brush daily (p=0.003), visited the dentist in the last 2 years (p<0.001) and brushed their teeth more than once a day (p<0.001). Hospitalised individuals also had fewer sound teeth (p<0.001), fewer filled teeth (p<0.001) and more missing teeth (p<0.001). 67.7% of hospitalized participants and 17.6% of non-hospitalized controls were edentulous. All hospitalised participants who had teeth had chronic periodontal disease compared to 80.2% of non-hospitalised controls (p<0.001). Hospitalised participants were significantly more likely to have moderately dry mouths than nonhospitalised controls (p<0.001). Conclusions The findings of this study reflect that oral health status in both groups was poor but overall it was significantly worse amongst those who were hospitalised. Hospitalised individuals also demonstrated poor knowledge, and more adverse attitudes and practices than non-hospitalised participants on dental care. Our study highlights an association between poor oral health and hospitalisation as a case-control study. Larger prospective study should be conducted to confirm this relationship.